Interstitial chromosomal deletion of the tuberous sclerosis complex 2 locus is a signature for radiation‐associated renal tumors in Eker rats. Issue 3 (3rd February 2020) - Inoue, Tatsuya; Kokubo, Toshiaki; Daino, Kazuhiro; Yanagihara, Hiromi; Watanabe, Fumiko; Tsuruoka, Chizuru; Amasaki, Yoshiko; Morioka, Takamitsu; Homma‐Takeda, Shino; Kobayashi, Toshiyuki; Hino, Okio; Shimada, Yoshiya; et al.
Abstract: Ionizing radiation can damage DNA and, therefore, is a risk factor for cancer. Eker rats, which carry a heterozygous germline mutation in the tumor‐suppressor gene tuberous sclerosis complex 2 ( Tsc2 ), are susceptible to radiation‐induced renal carcinogenesis. However, the molecular mechanisms involved in Tsc2 inactivation are unclear. We subjected Fischer 344 × Eker (Long Evans Tsc2 +/− ) F1 hybrid rats to gamma‐irradiation (2 Gy) at gestational day 19 (GD19) or postnatal day 5 (PND5) and investigated the patterns of genomic alterations in the Tsc2 allele of renal tumors that developed at 1 year after irradiation (N = 24 tumors for GD19, N = 10 for PND5), in comparison with spontaneously developed tumors (N = 8 tumors). Gamma‐irradiation significantly increased the multiplicity of renal tumors. The frequency of LOH at the chromosome 10q12 region, including the Tsc2 locus, was 38%, 29% and 60% in renal carcinomas developed from the nonirradiated, GD19 and PND5 groups, respectively. Array comparative genomic hybridization analysis revealed that the LOH patterns on chromosome 10 in renal carcinomas were classified into chromosomal missegregation, mitotic recombination and chromosomal deletion types. LOH of the interstitial chromosomal deletion type was observed only in radiation‐associated carcinomas. Sequence analysis for the wild‐type Tsc2 allele in the LOH‐negative carcinomas identified deletions (nonirradiated: 26%; GD19: 21%) and base‐substitution mutations (GD19: 4%). Reduced expression of Tsc2 was also observed in the majority of the LOH‐negative carcinomas. Our results suggest that interstitial chromosomal deletion is a characteristic mutagenic event caused by ionizing radiation, and it may contribute to the assessment of radiation‐induced cancer risk. Abstract : In this study, we used the Tsc2 heterozygous mutant Eker rat model to investigate the effects of radiation on the development of renal tumors and genomic alterations in those tumors. We found that in renal cancers of Eker rats, the tumor‐suppressor gene Tsc2 was inactivated by multiple mechanisms, including LOH with mitotic recombination or chromosomal deletion, point mutation, deletion and reduced Tsc2 expression. Importantly, our results suggest that interstitial chromosomal deletion is a characteristic mutagenic event caused by ionizing radiation, and it may be a useful indicator for more precise assessment of ionizing radiation‐induced cancer risk.